The role of the Sovereign state in 21st century environmental disasters. Issue 1 (2nd January 2022) - Park, Susan
ABSTRACT: 2019 was the second hottest year on record, with enhanced ice melts, sea level rises, heatwaves, droughts, and unprecedented large-scale wildfires of record intensity. Here I chart a new research agenda for understanding the interconnections between human behaviour, environmental disasters, and governing a more disaster-prone world. I argue that sovereign states' technological responses to environmental disasters as risks to be reduced systemically ignores human contributions to environmental hazards and vulnerabilities. Using a constructivist analysis, I analyse states' understandings of, and capacity to respond to, cascading environmental disasters at multiple scales according to what they collectively see, what they know, and how they act in terms of emergency preparedness and planning. Revealing the inadequacies of sovereign states' understanding of what constitutes environmental disasters absent their role in them, brings us closer to better governing cascading environmental disasters in the 21 st Century.